Chunking Strategy Effects on Retrieval Accuracy in Gemini 1.5 Long-Context Benchmarks - Assignee Research (Assignee Research, 2026)
This report synthesises findings from 14 peer-reviewed papers addressing the following research question: What is the impact of chunking strategies on the retrieval accuracy of Gemini 1.5 Flash and Gemini 1.5 Pro in long-context benchmarks like LongBench or RefSeq. 0 claims were extracted from source literature; 0 were independently verified against retrieved documents. An automated multi-reviewer quality assessment produced a score of 3.8/10. This report is a machine-generated literature synthe
Machine-generated literature synthesis.